Social Protection for the Informal Sector and the Informally Employed in Vietnam: Literature and data review - Nguyen Thi Lan Huong; Luu Quan Tuan; Matthias Meissner; Bui Sy Tuan; Dang Do Quyen; Nguyen Hai Yen (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2013)
In the last 20 years, Vietnam has been one of the fastest growing economies in Asia. But the coverage of social insurance is still low. Only around one in five workers is covered by the public social insurance scheme. Expanding the coverage of social insurance for informal sector workers and the informally employed is a key policy area as the role of traditional and informal security systems tends to get weaker. This paper provides a comprehensive literature and data review regarding informal sector research in Vietnam. Furthermore, it reflects the international understanding of the terms social protection, informal sector und informal employment. The impact of the informal sector on social protection and socio-economic development in Vietnam is evident. Nevertheless, in research, literature and data the picture is rather fragmented which indicates the necessity for further efforts.
Keywords: 360; Social protection; Social security; Social insurance; Informal sector; Informal economy; Literature review; Labour market; Social development; Vietnam; Informelle Wirtschaft; Schwarzarbeit; Soziale Sicherheit; Sozialversicherung; Vietnam